Public library consumer health information pilot project : results of a National Library of Medicine evaluation - WOOD, Fred B; LYON, Becky; SCHELL, Mary Beth; KITENDAUGH, Paula; CID, Victor H; SIEGEL, Elliot R (Bulletin of the Medical Library Association, 2000)
In October 1998, the National Library of Medicine (NLM) launched a pilot project to learn about the role of public libraries in providing health information to the public and to generate information that would assist NLM and the National Network of Libraries of Medicine (NN/LM) in learning how best to work with public libraries in the future. Three regional medical libraries (RMLs), eight resource libraries, and forty-one public libraries or library systems from nine states and the District of Columbia were selected for participation. The pilot project included an evaluation component that was carried out in parallel with project implementation. The evaluation ran through September 1999. The results of the evaluation indicated that participating public librarians were enthusiastic about the training and information materials provided as part of the project and that many public libraries used the materials and conducted their own outreach to local communities and groups. Most libraries applied the modest funds to purchase additional Internet-accessible computers and/or upgrade their health-reference materials. However, few of the participating public libraries had health information centers (although health information was perceived as a top-ten or top-five topic of interest to patrons). Also, the project generated only minimal usage of NLM's consumer health database, known as MEDLINEplus, from the premises of the monitored libraries (patron usage from home or office locations was not tracked). The evaluation results suggested a balanced follow-up by NLM and the NN/LM, with a few carefully selected national activities, complemented by a package of targeted activities that, as of January 2000, are being planned, developed, or implemented. The results also highlighted the importance of building an evaluation component into projects like this one from the outset, to assure that objectives were met and that evaluative information was available on a timely basis, as was the case here.